Floral Diversity and Patterns of Vegetation In and Around Siswan Community Reserve (SCR) in Punjab, India - Adhikari, Bhupendra S.; Kumar, Amit; Bhardwaj, Anil K. (Indian Forester, 2020)
As per Wildlife Protection (Amendment) Act, 2002, a new category of Protected Areas (PAs) have been introduced as Community Reserve (CR) in India. These areas, albeit uninhabited and completely owned by the Government of india are designated as CR for subsistence of local communities. The current study collates information on the vegetation structure and composition across different forests surrounding Siswan reservoir, a newly declared Community Reserve in Punjab, India. A total of 160 species of vascular plants were recorded, of which 45.6% were herbs, 21.3% trees, 12.5% shrubs, 10% grasses, 8.8% climbers and 1.9% sedges. Fabaceae was the most dominant family followed by Poaceae, Asteraceae and Malvaceae. Eight different forest communities were discernible through cluster analysis based on Bray-Curtis similarity, such as Acacia catechu-A. modesta, Acacia catechu-mixed, Acacia catechu-Anogeissus, Dalbergia, Butea-Dalbergia, Leaucaena, Mixed and Moringa-Mixed. The mixed community largely dominated the CR (ca. 45%). Among communities, Î²-diversity was highest for Acacia catechu-A. modesta community (2.12) and lowest for Acacia catechu-Anogeissus community (1.27). The species richness and Shannon-Weiner diversity index was high in Mixed, Acacia, Acacia catechu-mixed and Leaucaena communities. Owing to several medicinal properties and luxuriant growth of Tinospora sinensis, could be explored as a source oflivelihood for the locals through sustainable harvest. This study provides baseline information pertaining to ecological setting of the CR which will be helpful in the management of the area.